Aspectos gerais da infecção pela bactéria Treponema pallidum: uma revisão - Braga, Aline de Oliveira (2018)
Syphilis is a chronic disease caused by the bacterium Treponema pallidum subspecies pallidum, which can be transmitted sexually, vertically, responsible for congenital syphilis and less commonly through kissing or by blood transfusions. Data from the World Health Organization show that 17.7 million people in the world in 2012, aged 15-49 years, had acquired syphilis. In Brazil, syphilis had its compulsory notification installed in 2010, with an increase of more than 20 times in the number of cases of syphilis acquired per 100,000 inhabitants between 2010 and 2016. The cases of syphilis in pregnant women grew around four times in this period, being accompanied by cases of congenital syphilis. The infection occurs when T. pallidum comes in contact with the healthy mucosa or through microscopic lesions on the skin. Before the onset of clinical manifestations, the bacterium begins to multiply locally and through interjunctional penetration of the vascular endothelium, T. pallidum obtains access to several tissues after hematogenesis. The passage of the treponemes through the endothelial cells, results in an activation of these cells and expression of adhesion molecules, which causes the recruitment of phagocytic leucocytes responsible for th elimination of the microorganism. Thus, a complex innate and adaptive immune response is established mainly by the action of proinflammatory bacteria lipopeptides that stimulate innate immunity cells via the TLR2 pathway. They also act by modulating the response of CD4 T lymphocytes to the Th1 profile by inducing IL-2 and IFN-γ expression. Acquired untreated syphilis may progress to a variety of clinical manifestations responsible for separating the disease into primary syphilis, characterized by the presence of the lesion called protossifiloma; secondary syphilis, characterized by the dissemination of T. pallidum by all organs and tissues and the presence of disseminated cutaneous lesions; latent syphilis, with a high concentration of antibodies and absence of symptoms. It is still infectious and tertiary syphilis is not very infectious, and can evolve into cardiovascular or neurosyphilis forms. Until now there are no reports of resistance to antibiotic penicillin treatment, however syphilis remains a serious public health problem, so efforts to develop an effective vaccine are being carried out worldwide.